Avaliação de polímeros impressos para pré- concentração/extração de Se, U e Cd - Lago, Ayla Campos do (Universidade Federal de São Carlos, 2015)
This thesis describes the development of imprinted polymers for preconcentration of Se, Cd and U. The relevant factors to the FIA system and preconcentration were optimized by Doehlert matrix. Chapter I describes an atomically imprinted polymer synthesis for preconcentration of Se (0) and determination by HG-AAS. The method presents the following analytical features: linear range from 0.17 to 6.0 μg L-1 , limit of detection and quantification of 53 and 170 ng L-1 , respectively, of preconcentration factor of 232 and reading frequency analysis of 12 h-1 ; which were all applied in food samples. The accuracy was checked with certified reference material. Chapter II describes the synthesis of a hybrid imprinted polymer for uranium concentration and determination by UV-visible spectrophotometry. The polymer had adsorptive capacity of 1.55 mg g-1 , linear analytical range from 2.0 to 100.0 μg L -1 detection limit of 0.40 μg L-1 quantification limit of 1.25 μg L-1 , preconcentration factor of 97, concentration efficiency of 19.40 min-1 . The method was applied to water samples from rivers and lakes, with accuracy confirmed by alpha spectrometry. Finally, in Chapter III, a method for cadmium determination by TS-FF-AAS after preconcentration in imprinted polymer synthesized via bulk is proposed. The figures of merit were linear range 0.081 to 10 μg L-1 , detection and quantification limit of 24 and 81 ng L-1 , respectively. Preconcentration factor of 165 and frequency measures analyzes 25 h-1 . The method was applied in tea, hair, cigarette and jewelry samples. The accuracy was checked with certified reference material.
Imprinted polymer evaluation for preconcentration/extraction of Se, U and Cd
Keywords: Química analítica; Pré-concentração; Polímeros; TS-FF-AAS; HG-AAS; UV-visível; Preconcentration; Imprinted polymers; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA